Can You See a Chimpanzee? : All About Primates - Rabe, Tish; Ruiz, Aristides; Mathieu, Joseph, 1949- (New York : Random House Children's Books, 2014)
"Join The Cat in the Hat as he explores the amazing world of Chimpanzees"--
Includes bibliographical references and index.
Keywords: Apes -- Juvenile literature; Monkeys -- Juvenile literature; Primates -- Juvenile literature; Apes; Monkeys; Primates; JUVENILE NONFICTION / Animals / Apes, Monkeys, etc